UPAYA PEMERINTAH DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA ULUJANGANG KECAMATAN BONTOLEMPANGAN - Achsanuddin UA, Anur; Fitrianti, A Nur; Melinda, Feni (Jurnal Ekonomi Balance, 2017)
This study aims to determine the efforts of the village government in improving the welfare of the community in Ulujangang Village, Bontolempangan Subdistrict, Gowa Regency by using a qualitative descriptive approach by conducting data analysis inductively and descriptively by revealing the facts in the field to provide an overview of the problems that occur in the field. The results showed that the efforts made by the Ulujangang Village government in improving the welfare of the people in Ulujangang Village through empowering the red sugar makers and empowering the chair craftsmen had been positively responded by the community as a social-based program.